Extracorporeal Treatment for Poisoning - Catarina Cardoso; Sílvia Coelho (Publicações Ciência e Vida, 2022)
Accidental or intentional poisoning and drug overdose are a significant source of morbidity, mortality and health care expenditure worldwide. Extracorporeal removal treatments have been used to treat poisoning for decades and different modalities are available, including hemodialysis, hemofiltration, hemoperfusion, continuous renal replacement therapy and therapeutic plasma exchange. A comprehensive understanding of their purpose is key to choose the right modality for each clinical scenario. Lithium, salicylates, metformin and toxic alcohols are amongst the most common poisons treated with extracorporeal removal. Unfortunately, due to poison characteristics and specific modality limitations, extracorporeal treatments are useful to treat only a small number of poisons. Nevertheless, they have been increasingly used for supportive care in poisoning caused by substances not amenable for removal. Evidence regarding extracorporeal treatment in poisoning is modest. However, its use has been systematically reviewed in several poisons within the last decade by the Extracorporeal Treatment in Poisoning workgroup. The preferred treatment for extracorporeal removal of poisons is intermittent hemodialysis, according to the most recent guidelines and case reports available, as it effectively removes most of the common substances involved in poisoning and corrects electrolytes and acid base imbalances. This narrative review gives an overview of the available extracorporeal modalities used for poisoned patients, reflecting on their main indications and limitations as well as a practical view on the management of the most common poisons found in clinical practice.